Biosensor Technologies In Sports : Advancements, Challenges, and Future Directions - Kasumawati, Lias (Lembaga Jurutera Malaysia, 2023)
Biosensor technologies have revolutionized various domains, including sports applications. The use of biosensors forsports applications are aimed at enhancing athlete performance, monitoring health and fitness levels, and preventing injuries. In Malaysia, several research institutions, universities, and sports organisations have been involved in the development and implementation of biosensors for sports. These institutions work on various aspects, including sensor design, data analysis, and integration with wearable devices.